Body fat measurements in elite adolescent volleyball players: Correlation between skinfold thickness, bioelectrical impedance analysis, air-displacement plethysmography, and body mass index percentiles - Portal, S.; Rabinowitz, J.; Adler-Portal, D.; Pilz Burstein, R.; Lahav, Y.; Meckel, Y.; Nemet, D.; Eliakim, A. (Journal of Pediatric Endocrinology and Metabolism, 2010)
Background- Determination of body composition is an essential parameter in training athletes because low fat-muscle ratio might improve physical performance in many types of sports. Since training is often conducted in the field, it is important to determine whether simple field measurements of body composition assessment correlate with laboratory measurements.